Jesus in the Synagogue of Capernaum: the pericope and its programmatic character for the Gospel of Mark: and exegetico-theological study of MK 1:21-28 - Chijioke Iwe, John (Tesi gregoriana, 1999)
This book considers Jesus first appearance and activity in Galilee and affirms that Mk. 1:2128 has a programmatic character for the Gospel of Mark.